PEDAGIGICAL MODEL OF ARTISTIC-ESTHETIC COMPETENCE DEVELOPMENT OF FUTURE MUSIC TEACHERS ON THE BASES OF DISCIPLINE INTEGRATION (Scientific journal of the Fergana State University, 2023)
In this article, the strengthening of high moral qualities, which are considered the main criterion of maturity in young people, the study of the necessity of spirituality in the life of an individual, society and the state based on social and moral criteria, the need for a high concept of spirituality for young people, spiritual highness are factors which ensure the stability of the country explaining that it is a vital necessity of high spirituality and the main criterion for the development of society, which is scientifically grounded. Also, in the article, it is emphasized that, in addition to achieving professional skills in the training of music education specialists, it is necessary to make wide use of the possibilities of music education disciplines in order to train competent specialists in the possession of universal qualities.